Unconventional polycyclic aromatic compounds distribution profiles in sediment cores collected from Todos os Santos Bay, Northeastern Brazil - Niño-Zambrano, Eileen Rocio; Bahia, Pedro V.B.; Nascimento, Madson M.; Sampaio, Fábio X.A.; Duarte, Ricardo da S.; Hatje, Vanessa; Machado, Maria Elisabete; Andrade, Jailson B. de; Rocha, Gisele O. da (Journal of hazardous materials, 2025)
Polycyclic aromatic compounds (PACs) include conventional polycyclic aromatic hydrocarbons (PAHs) and nitrated (NHPAs), oxygenated (OHPAs), heterocyclic polycyclic aromatic sulfur (PASHs) derivatives, considered unconventional. Sediment cores were collected at four Todos os Santos Bay sites (BTS, Northeastern Brazil). Eighteen NPAHs, six OPAHs, seven PASHs, and nineteen PAHs were determined. The total concentrations of NPAHs, PASHs, and PAHs increased from the bottom towards the top of the cores, ranging from <LOD to 444 ng g−1 dw, <LOD to 104 ng g−1 dw, <LOD to 1160 ng g−1 dw and 10.6–1825 ng g−1 dw. Higher levels of NPAHs, PASHs, and PAHs were observed within the Port area associated with maritime and industrial activities, while 9,10-anthraquinone and low molecular weight PAH levels were elevated near a refinery. Principal Component Analysis revealed a mixture of emission sources in the top sediment layers in the western part of the bay, fossil fuel combustion in the Port area, and petrogenic sources near a refinery. The occurrence of PACs in bottom sediment cores near the river mouth and refinery (dating back to the 1850s) suggests sources from the sugar cane industry and petrogenic natural reserves. High PAC levels in a core near a refinery indicated the impact of BTS industrialization. [Display omitted] •50 PACs were measured in marine sediment cores from a Northeastern Brazil bay.•The main sources of PACs were burning fossil fuels and refining fuels.•PACs in the bottom layers of the river core (1850s) were from sugar cane burning.•PACs in refinery core bottom layers (1850s) were from petrogenic reserves.